Using wordle in counseling ethics education - Asfaw, Amanuel H.; Warren, Jane A.; McKim, Courtney; Morris-Howe, Lay-nah Blue; Meggitt, David; Mullins, Phillip; Zakaria, Noor Syamilah; Rossetter, Nikki (American Counseling Association, 2017)
There are educational techniques that can positively impact teaching in the counseling profession. This paper describes an educational technique using Wordle. Wordle is word cloud visualization of text and is used in research and education. We present the use of Wordle in counselor ethics education to show how it can illustrate change in thinking and, ultimately, learning.